Analyzing the effects of computer-assisted dynamic assessment on L2 writing tasks for Chinese learners - Sun Wei; Yousun Shin (Cogent Education)
This study investigates the effects of computer-assisted Interventionist Dynamic Assessment (IDA) and Hybrid Dynamic Assessment (HDA) on the organizational skills of L2 writing among Chinese university students, addressing gaps in traditional product-focused writing instruction. Eighty-four participants were randomized into IDA or HDA groups, completing three argumentative writing tasks (pretest, DA test, posttest) over 5 weeks. The IDA group received standardized computer-mediated prompts (Mediational Moves), while the HDA group combined computer-mediated prompts with instructor-led, personalized mediation. Results revealed both groups improved significantly, but HDA demonstrated superior gains in organizational skills, attributed to its interactive scaffolding aligned with sociocultural theory’s Zone of Proximal Development (ZPD). Repeated-measures ANOVA highlighted significant progression over time, though posttest scores slightly declined, suggesting developmental process of progression in cognitive development. Mediational move analysis indicated HDA’s adaptive support fostered deeper cognitive engagement, evidenced by higher Learning Potential Scores (LPS). The study highlights the effectiveness of HDA in improving organizational skills through computer-assisted mediation combined with teacher-led dialogic interaction. It offers pedagogical insights into integrating dynamic, technology-enhanced assessment methods in EFL settings to better connect assessment with instruction. Findings advocate for blended models that prioritize individualized feedback, leveraging technology and human mediation to address L2 writers’ evolving needs within their ZPD.